Membangkitkan Minat Belajar Siswa Melalui Lomba Cerdas Cermat Sekolah Menengah Atas (SMA) di Kabupaten Seram Bagian Barat - Kahar, Siti Rahmawati; Pieter, Marsiline (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2023)
Learning is an important process for the change of human behavior which covers something which is thought and done. The change of behavior occur. This is because it is started from one experience to the others, so it causes many changes.  Quiz competition is one of the efforts which is done to train students’ pendagogic ability. The lack of interest of students to study here raises considerable concerns so that an activity is held topromote the school through a community partnership program (PKM).PKM activity is implemented aims to attract student learning by way of conducting a quiz contest as a form of promotion. The quiz is a learning technique that is used to improve students' activity and learning outcomes through the contest. Participants of this event followed by 37 schools with one team consisting of 3 students. The quiz consists of 3 rounds namely preliminary round, semifinal round and final round. In the preliminary round obtained 5 groups which then matched to the semifinals. Furthermore, in the semifinal round obtained 3 groups who competed in the final round to win the champion candidate. The results for 1st place were achieved by SMA Negeri 16 SBB, the 2nd place was won by SMA PGRI 2 Kairatu, and 3rd place by SMA Negeri 2 Seram Barat. The result of this PKM activity is expected to attract students' interest in studying. The results of PKM activities are expected to attract students.